Hubungan Lama Penyimpanan Sampel Arsip Jaringan Dalam Blok Parafin Terfiksasi Formalindengan Kualitas Hasil Ekstraksidna Mitokondria Jaringan - Hafy, Zen; Larasati, Veny; Puspita, Riana Sari; S, Novizar; M, Haekal; A, Rafdi; R, Sentani (Sriwijaya Journal of Medicine, 2018)
Formalin-fixed paraffin-embedded (FFPE) archival tissue presents a readily available resource in molecular study nowadays. The quality of nucleid acid, especially mitoconhdrial DNA (mtDNA) extracted from FFPE tissue could be affected by the storage time. Thus, this study investigated if the FFPE tissue’s storage time had an effect on the quality of the extracted mtDNA at Department of Pathology RSUP Dr. Mohammad Hoesin Palembang. DNA was extracted from 16 randomly selected archival FFPE tissues in Laboratory of Pathology Anatomy, RSUP dr. Mohammad Hoesin Palembang. The samples were grouped based on their storage time (less than 1 year and 1 to 5 yrs.’ old). The isolated DNA from each group was amplified using PCR with two primer pairs specifically designto amplify mtDNA of 320 bp and 142bp length, respectively. The PCR products were visualized by electrophoresismethod. None of the samples from both groups could be amplified witht the 320bp primers. However, the PCR result of the 149 bp primers showed positive for all of the samples from each study group. The study indicated that the storage time does not affect the quality of mtDNA isolated from the FFPE samples archived in Department of Pathology RSUP Dr. Mohammad Hoesin Palembang. Furthermore, the study showed that the mtDNA extracted from FFPE tissue has been degraded, therefore, the samples are not suitable for genetic studies require a long mtDNA amplicon.